Opportunistic Dermatophyte Infections in Immunocompromised Patients With Rheumatoid Arthritis: A Review Article - Athouf, Dhuha A. (Indonesian Journal on Health Science and Medicine, 2025)
Background: Opportunistic dermatophyte infections pose an increasing issue in immunocompromised individuals, especially those with rheumatoid arthritis (RA). Rheumatoid arthritis patients frequently get immunosuppressive treatment, such as corticosteroids and biologics, rendering them susceptible to fungal infections. Dermatophytes, a category of keratinophilic fungus, can induce severe and unusual infections in these patients, frequently resulting in chronic, treatment-resistant diseases. This review examines the epidemiology, risk factors, clinical symptoms, and diagnostic difficulties associated with opportunistic dermatophyte infections in individuals with rheumatoid arthritis. Additionally, it emphasizes contemporary therapeutic methods and preventive measures to reduce the risk of infection in this at-risk population. Timely diagnosis and customized antifungal therapy are essential for enhancing patient outcomes. Objectives: This study seeks to examine opportunistic dermatophyte infections in immunocompromised individuals with rheumatoid arthritis (RA), especially those receiving immunosuppressive treatment. Conclusion: The interaction between compromised immune responses and heightened vulnerability to fungal infections requires proactive prevention and early intervention techniques. By maintaining good hygiene, wearing suitable footwear, employing antifungal treatments, and obtaining prompt medical consultation, patients can significantly reduce the dangers associated with dermatophyte infections. Highlights: High Risk in RA Patients, Immunosuppressive drugs increase susceptibility to dermatophyte infections. Difficult to Diagnose and Treat, Infections can become chronic and drug-resistant, requiring timely and tailored antifungal therapy. Prevention Is Essential, Good hygiene, proper footwear, and early medical attention help reduce infection risk. Keyword: Dermatophyte, Fungi, Immunocompromised, Rheumatoid Arthritis, Opportunistic